2020
DOI: 10.3390/diagnostics10110930
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Fatigue Is Associated with Altered Functional Connectivity in Interoceptive and Reward Pathways in Multiple Sclerosis

Abstract: Cognitive fatigue is common and debilitating among persons with multiple sclerosis (pwMS). Neural mechanisms underlying fatigue are not well understood, which results in lack of adequate treatment. The current study examined cognitive fatigue-related functional connectivity among 26 pwMS and 14 demographically matched healthy controls (HCs). Participants underwent functional magnetic resonance imaging (fMRI) scanning while performing a working memory task (n-back), with two conditions: one with higher cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 46 publications
3
21
0
Order By: Relevance
“…The dopamine imbalance hypothesis of fatigue in MS is supported by several imaging studies showing the presence of both structural and functional alterations within the mesocorticolimbic pathways of MS patients experiencing fatigue ( Dobryakova et al, 2015 , Genova et al, 2013 , Pardini et al, 2010 ). Recently, Chen et al demonstrated by using functional-MRI altered cognitive fatigue-related functional connectivity in the monoamine-associated interoceptive and reward pathways in MS and speculated that such alterations may be the result of inefficient brain connectivity when meeting increased task demands ( Chen et al, 2020 ). Similarly, Jaeger et al performed a sub-region functional-MRI analysis finding that MS-related fatigue was associated with impaired functional connectivity of the striatum with sensorimotor, attention, and reward networks.…”
Section: Discussionmentioning
confidence: 99%
“…The dopamine imbalance hypothesis of fatigue in MS is supported by several imaging studies showing the presence of both structural and functional alterations within the mesocorticolimbic pathways of MS patients experiencing fatigue ( Dobryakova et al, 2015 , Genova et al, 2013 , Pardini et al, 2010 ). Recently, Chen et al demonstrated by using functional-MRI altered cognitive fatigue-related functional connectivity in the monoamine-associated interoceptive and reward pathways in MS and speculated that such alterations may be the result of inefficient brain connectivity when meeting increased task demands ( Chen et al, 2020 ). Similarly, Jaeger et al performed a sub-region functional-MRI analysis finding that MS-related fatigue was associated with impaired functional connectivity of the striatum with sensorimotor, attention, and reward networks.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this framework, it has been proposed that the feeling of fatigue (state fatigue) arises from an inability to correct deviations from a balanced homeostatic state. 47 Some evidence suggests that functional connectivity within interoceptive networks is disturbed in persons with MS. 8,[50][51][52] In a neuroimaging study of brain networks, for example, Chen et al 39 found that an increase in the VAS rating of fatigue when persons with MS performed a working-memory task was associated with increased residual functional connectivity as assessed by functional MRI between both the insula and the dorsal anterior cingulate cortex with other brain areas. The connectivity patterns from selected brain regions (insula, dorsal anterior cingulate cortex, striatum, dorsolateral prefrontal cortex, and ventromedial prefrontal cortex) of the MS participants became more diffuse as the cognitively demanding task progressed, likely due to interoceptive efforts to attenuate challenges to a balanced homeostatic state.…”
Section: The Symptom Of Fatiguementioning
confidence: 99%
“…However, autonomic dysfunction only explains a moderate amount of the variance in state measures of fatigue (VAS scores). 56 The sense of fatigue that arises from interoceptive networks can be modulated by reward (motivational) pathways 37,39,[57][58][59] and pain pathways. [60][61][62] For example, Pardini et al 63 reported that reward responsiveness was negatively correlated with a questionnaire-derived estimate of fatigue in persons with MS who had clinically significant levels of fatigue.…”
Section: The Symptom Of Fatiguementioning
confidence: 99%
See 2 more Smart Citations